Observation of a gel of quantum vortices in a superconductor at very low magnetic fields - José Benito Llorens; Lior Embon; Alexandre Correa; Jesús David González; Edwin Herrera; Isabel Guillamón; Roberto F. Luccas; Jon Azpeitia; Federico J. Mompeán; Mar García-Hernández; Carmen Munuera; Jazmín Aragón Sánchez; et al. (Physical Review Research, 2020)
A gel consists of a network of particles or molecules formed for example using the sol-gel process, by which a solution transforms into a porous solid. Particles or molecules in a gel are mainly organized on a scaffold that makes up a porous system. Quantized vortices in type-II superconductors mostly form spatially homogeneous ordered or amorphous solids. Here we present high-resolution imaging of the vortex lattice displaying dense vortex clusters separated by sparse or entirely vortex-free regions in β-Bi_{2}Pd superconductor. We find that the intervortex distance diverges upon decreasing the magnetic field and that vortex lattice images follow a multifractal behavior. These properties, characteristic of gels, establish the presence of a novel vortex distribution, distinctly different from the well-studied disordered and glassy phases observed in high-temperature and conventional superconductors. The observed behavior is caused by a scaffold of one-dimensional structural defects with enhanced stress close to the defects. The vortex gel might often occur in type-II superconductors at low magnetic fields. Such vortex distributions should allow to considerably simplify control over vortex positions and manipulation of quantum vortex states.